Special Relationships, Motivation and the Pursuit of Global Egalitarianism - Lenard, Patti (Les ateliers de l'éthique / The Ethics Forum, 2013)
One of the most significant challenges facing global egalitarian theorists is the motivational gap: there is a noted gap between the duties imposed by a global commitment to the equal moral worth of all people and the willingness of the wealthy to carry out these duties. For Pablo Gilabert, the apparent absence of motivation to act justly on a global scale presses us to consider the importance of feasibility in developing a persuasive account of global justice, part of which requires being attentive to what motivates us to act in support of global egalitarianism. In this article, I am critical of Gilabert’s account of the role that relationships between individuals play in conceiving our global justice duties. I begin with an account of some confusion in Gilabert’s account of the actual costs likely to be imposed on citizens of wealthy states as a result of the duties he demands of us and why it is important to resolve that confusion. I will then consider, and critique, Gilabert’s account of special responsibilities. I shall argue that, fundamentally, there is an ineliminable tension between the special responsibilities individuals legitimately possess and the duties they have to eradicate global poverty.